Integrated metabolomic and transcriptomic analysis reveals perturbed glycerophospholipid metabolism in mouse neural stem cells exposed to cadmium - Li, Yixi; Zhang, Jiming; Zhang, Yuwei; Zhang, Bing; Wang, Zheng; Wu, Chunhua; Zhou, Zhijun; Chang, Xiuli (Ecotoxicology and environmental safety, 2023)
Cadmium (Cd) is a ubiquitous heavy metal with neurotoxicity. Our previous study reported that Cd could inhibit the proliferation of mouse neural stem cells (mNSCs). However, the underlying mechanisms are obscure. In recent years, the rapid growth of multi-omics techniques enables us to explore the cellular responses that occurred after toxicant exposure at the molecular level. In this study, we used a combination of metabolomics and transcriptomics approaches to investigate the effects of exposure to Cd on mNSCs. After treatment with Cd, the metabolites and transcripts in mNSCs changed significantly with 110 differentially expressed metabolites and 2135 differentially expressed genes identified, respectively. The altered metabolites were mainly involved in glycerophospholipid metabolism, arginine and proline metabolism, arginine biosynthesis, glyoxylate and dicarboxylate metabolism. Meanwhile, the transcriptomic data demonstrated perturbed membrane function and signal transduction. Furthermore, integrated analysis of metabolomic and transcriptomic data suggested that glycerophospholipid metabolism might be the major metabolic pathway affected by Cd in mNSCs. More interestingly, the supplementation of lysophosphatidylethanolamine (LPE) attenuated Cd-induced mitochondrial impairment and the inhibition of cell proliferation and differentiation in mNSCs, further supporting our analysis. Overall, the study provides new insights into the mechanisms of Cd-induced neurotoxicity. [Display omitted] •Cd altered the metabolite and transcript profiles in mNSCs.•Glycerophospholipid metabolism may be the major pathway affected by Cd exposure.•Cd-induced PE deficiency results in mitochondrial impairment in mNSCs.•LPE rescued Cd-induced abnormality of cell proliferation and differentiation.